2022
DOI: 10.4081/jphia.2022.2040
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tuberculosis case notification rate: spatial mapping of hotspot, coverage and diagnostics in Katsina State, north-western Nigeria

Abstract: Tuberculosis (TB) is prevalent in Nigeria, and Katsina, along with other 12 states in the country, accounts for a high proportion of unnotified TB cases: constituting the high priority-intervention States in the country. Interventions focused on TB detection and coverage in the state could benefit from a better understanding of hotspot Local Government Areas (LGAs) that trigger and sustain the disease. Therefore, this study investigated the spatial distribution of TB Case Notification Rates (CNRs), diagnostics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The review largely confirmed many general characteristics previously observed on the inter relationship between Tuberculosis and poor socio-economic conditions, precarious living conditions and overcrowding., but also documented the extensive methodological limitations of studies that used varying methodologies that are divergent and heterogenous especially in terms of the population size and context which this present study evaluated 79 published articles [ 19 – 93 ] presented in Table S 2 and S 3 . Most of the methods used in the studies reviewed are best suited for low/high endemic regions depending on the model applied., among other limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The review largely confirmed many general characteristics previously observed on the inter relationship between Tuberculosis and poor socio-economic conditions, precarious living conditions and overcrowding., but also documented the extensive methodological limitations of studies that used varying methodologies that are divergent and heterogenous especially in terms of the population size and context which this present study evaluated 79 published articles [ 19 – 93 ] presented in Table S 2 and S 3 . Most of the methods used in the studies reviewed are best suited for low/high endemic regions depending on the model applied., among other limitations.…”
Section: Discussionmentioning
confidence: 99%